Reducing the Climate Impact of Ruminant Feed and Improving Animal Health in Europe by Using Maize and Lupine Additives - Barbara Płacheta; Ilona Motyl; Joanna Berłowska (BioResources)
Ruminant farming is a significant contributor to global food production but also a major source of methane emissions. It is responsible for nearly 44% of greenhouse gases from the agricultural sector. The integration of maize and lupine into the diets of ruminants offers a sustainable strategy for improving feed efficiency, reducing methane emissions, and enhancing animal productivity. Fermented maize silage has been shown to lower methane emissions by 10 to 20% compared to conventional high-starch diets. Lupine supplementation can further reduce methane emissions by influencing rumen fermentation. The inclusion of lupine, a nitrogen-fixing legume, additionally enhances soil fertility and reduces the need for synthetic fertilizers, making it an environmentally sustainable alternative to soybean meal. Studies indicate that diets incorporating maize silage and lupine can improve feed conversion efficiency and increase milk yield by up to 5% in dairy cattle. However, large-scale adoption of these feed additives requires further research to optimize fermentation processes, ensure economic feasibility, and overcome regulatory barriers. This study highlights the potential of maize and lupine as viable solutions for enhancing livestock sustainability while mitigating climate impacts.